EXISTENTIALISM IN THE PERSPECTIVE OF THE QUR'AN: AN EXAMINATION OF FREEDOM AND RESPONSIBILITY IN QS. ASY-SYAMS, AL-INSAN, AND AL-KAHFI - Rangkuti, Alpan Noor Habib; Syihabuddin (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines existentialism from the perspective of the Qur'an by emphasizing the concept of individual freedom and responsibility. Existentialism, which developed in Western philosophy through the thoughts of figures such as Martin Heidegger and Jean-Paul Sartre, emphasizes individual freedom in determining the meaning of life. In Islam, this freedom is balanced with moral and spiritual responsibility as explained in the Qur'an. This study uses a descriptive qualitative approach with a content analysis method to examine the verses of the Qur'an, such as QS. Asy-Syams, QS. Al-Insan, and QS. Al-Kahfi. The results of the study show that the Qur'an emphasizes human freedom in choosing a path in life, but every choice has consequences that must be accounted for before Allah. In addition, this study identifies the differences between existentialism in Islam and the West. In Islam, individual freedom is always related to submission to Allah and ethical values, while Western existentialism emphasizes individual autonomy without transcendental attachment. This study confirms the relevance of existentialism in facing the challenges of modern life, especially in the search for the meaning of life and identity. This research is expected to enrich academic studies on the integration of existentialism and Islamic values ​​in various fields, such as education, ethics, and social life.